Testicular cancer and YouTube: What do you expect from a social media platform?. (22nd March 2022) - Di Bello, Francesco; Collà Ruvolo, Claudia; Cilio, Simone; La Rocca, Roberto; Capece, Marco; Creta, Massimiliano; Celentano, Giuseppe; Califano, Gianluigi; Morra, Simone; Iacovazzo, Carmine; Coviello, Antonio; Buonanno, Pasquale; et al.
Abstract : Objective: To evaluate the quality information on testicular cancer uploaded on YouTube™ videos. Methods: YouTube™ videos were searched using "Testicular cancer" as a keyword. The Patient Education Materials Assessment Tool, the Misinformation scale, and the DISCERN tool were used to assess the quality information of YouTube™ videos on testicular cancer. Results: According to the selection criteria, 121 YouTube™ videos were collected for the analysis and stratified according to uploading year (2009–2014 vs 2015–2020). According to the Patient Education Materials Assessment Tool for audio‐visual content, the overall Understandability score was 60% (interquartile range 45.5–75) and the overall Actionability score was 100% (interquartile range 66.7–100). According to the Misinformation scale, the lowest median was recorded for item 6 ("Effects on fertility") and the overall median Misinformation score was 2 (interquartile range 1.3–2.8). No statistically significant differences were observed according to uploading year (all P  > 0.05). Of all, only 54 (44.6%) videos mentioning treatment were subsequently analyzed. Of these videos, the overall Understandability was 71.4% (interquartile range 56.3–84.6) and the overall Actionability was 100% (interquartile range 66.7–100). The overall Misinformation score was 2.8 (interquartile range 2.2–3.5). The median DISCERN score recorded for question 16 was 5 (interquartile range 3–5). Conclusions: YouTube™ is a fast and open‐access source for mass information. The overall quality of the testicular cancer contents provided is sadly unsatisfactory, in the present likewise in the past. However, YouTube™ videos mentioning treatment options showed higher quality content, than the remaining one. Nevertheless, all the videos analyzed underestimated the testicular cancer effects on fertility. Nowadays, YouTube™ cannot be recommended as a reliable source of information on testicular cancer.